Beatriz Figueroa Campos (comp.). La fecundidad en México : cambios y perspectivas. México : El Colegio de México, 1989. 454 p. - Muñoz Contreras, María Elena (El Colegio de México A.C., 1990)
BEATRIZ FIGUEROA CAMPOS (comp.), La fecundidad en México: cambios y perspectivas, El Colegio de México, 1989.